The Partitioning of Carbon Biomass among the Pico- and Nano-plankton Community in the South Brazilian Bight during a Strong Summer Intrusion of South Atlantic Central Water - Bergo, Natascha M.; Signori, Camila N.; Amado, André M.; Brandini, Frederico P.; Pellizari, Vivian H. (Frontiers in Marine Science, 2017)
To investigate how pico- and nanoplankton respond to oceanographic conditions in the Southwestern Atlantic Ocean, we assessed the influence of a summer intrusion of the South Atlantic Central Water (SACW) on the spatial and vertical dynamics of planktonic abundance and carbon biomass across environmental gradients. Seawater samples were collected from six depths within the euphotic zone at nine oceanographic stations in a transect on the Brazilian continental shelf in January 2013. The abundance of pico- and nanoplankton populations was determined by flow cytometry, and carbon biomass was calculated based on conversion factors from the literature. The autotrophic Synechococcus spp., picoeukaryotes and nanoeukaryotes were more abundant in the surface layers of the innermost stations influenced by Coastal Water (maximum of 1.19x105, 1.5x104, and 8.61x103 cell·mL−1, respectively), whereas Prochlorococcus spp. dominated (max. of 6.57x104 cell·mL−1) at the outermost stations influenced by Tropical Water and in the uplifting layers of the SACW around a depth of 100 m. Numerically, heterotrophic bacterial populations were predominant, with maximum concentrations (2.11x106 cell·mL−1) recorded in the surface layers of the inner and mid shelves in Coastal Water and the upper limits of the SACW. Nutrient-rich (high silicate and phosphate) and relatively less saline waters enhanced the picoeukaryotic biomass, while Synechococcus and heterotrophic bacteria were linked to higher temperatures, lower salinities, and higher inputs of ammonia and dissolved organic carbon. The relative importance of each group to carbon biomass partitioning under upwelling conditions is led by heterotrophic bacteria, followed by picoeukaryotes, Synechococcus and Prochlorococcus, and when the SACW is not as influential, the relative contribution of each phytoplanktonic group is more evenly distributed. In addition to habitat preferences, the physical structure of oligotrophic waters has a large impact on the vertical and spatial distribution patterns of picoplankton, reflecting the strong effect of the SACW intrusion.